2000
DOI: 10.1046/j.1468-3156.2000.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of specialist occupational therapists within residential learning disabilities: a justified case?

Abstract: The principles of ‘social role valorization’ ( Wolfensberger 1983) advocate access to general primary health and social care facilities for individuals with learning disabilities alongside the rest of the population. Throughout the UK, there has been a variety of responses to employing specialist staff for people with a learning disability. Specialist learning disability occupational therapists with specific experience and skills in learning disabilities are employed by some National Health Service (NHS) trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…While multidisciplinary or interdisciplinary approaches are generally preferred in the support of persons with ID, the recent literature also provides descriptions of the role of specific disciplines. These include a strengths-based approach for social workers [Russo, 1999], use of specialist occupational therapists in residential settings for persons with ID in the United Kingdom [Adams, 2000], and improved nursing care of elderly people with ID in the United States [Fisher, 2004b]. A series of professional development articles on ID offer continuing education nursing credits in the United Kingdom on topics such as health promotion [Bollard, 2002], sexuality of persons with ID [Savarimuthu and Bunnell, 2003], and improving services for people with ID [Williamson and Johnson, 2004].…”
Section: Provider-based Practicesmentioning
confidence: 99%
“…While multidisciplinary or interdisciplinary approaches are generally preferred in the support of persons with ID, the recent literature also provides descriptions of the role of specific disciplines. These include a strengths-based approach for social workers [Russo, 1999], use of specialist occupational therapists in residential settings for persons with ID in the United Kingdom [Adams, 2000], and improved nursing care of elderly people with ID in the United States [Fisher, 2004b]. A series of professional development articles on ID offer continuing education nursing credits in the United Kingdom on topics such as health promotion [Bollard, 2002], sexuality of persons with ID [Savarimuthu and Bunnell, 2003], and improving services for people with ID [Williamson and Johnson, 2004].…”
Section: Provider-based Practicesmentioning
confidence: 99%
“…They argue that when staff share tasks and operate outside of their areas of expertise, there is a loss of efficiency in practice. Other authors have seconded these claims and also pointed to the larger detriment to services and service users who depend on the expertise of health professionals and the specialist skills and knowledge offered (Adams, 2000;Grieg & Peck, 1998). Harries and Gilhooly (2003) stated, "If too much time is spent on generic work, there will be clients with unmet needs" (p. 102).…”
Section: Effectiveness In Client Carementioning
confidence: 99%
“…Tannous (2000) state that occupational therapists' intervention with people with learning disabilities and high‐support needs was related to the areas of self‐maintenance productivity/education and leisure/play. Adams (2000) found that community staff perceived their service users' needs for occupational therapy as predominately related to physical disability. Specialist areas such as challenging behaviour, sensory integration and sexuality were all cited as areas of service users' needs but were managed well by specialist nursing staff.…”
Section: Discussionmentioning
confidence: 99%